Nociception and pain: lessons from optogenetics - Zachariou, Venetia; Carr, Fiona (Frontiers in Behavioral Neuroscience, 2014)
The process of pain perception begins in the periphery by activation of nociceptors. From here nociceptive signals are conveyed via the dorsal horn of the spinal cord to multiple brain regions, where pain is perceived. Despite great progress in pain research in recent years, many questions remain regarding nociceptive circuitry and behavior, in both acute nociception and chronic pain states. Techniques that allow for selective activation of neuronal subpopulations in vivo can provide a better understanding of these complex pathways. Here we review the studies to date that have employed novel optogenetic tools to improve our understanding of the pain pathway at the peripheral, spinal and supraspinal levels.